The Buffett plan for reducing the trade deficit - Dimitri B. Papadimitriou; Greg Hannsgen; Gennaro Zezza (Levy Economics Institute of Bard College, 2008)
This paper considers a plan proposed by Warren Buffett, in which importers would be required to obtain certificates proportional to the amount of non-oil goods (and possibly also services) they brought into the country. These certificates would be granted to firms that exported goods. Exporting firms could then sell certificates to importing firms on an organized market. In this paper, starting from a relatively neutral projection of all major variables for the U.S. economy, we estimate that the plan would raise the price of imports by approximately 9 percent, quickly reducing the current account deficit to about 2 percent of GDP. We discuss several problems that might arise with the implementation of the Buffett plan, including possible instability in the price of certificates and retaliation by U.S. trade partners. We also consider an alternative version of the Buffett plan, in which certificates would be sold at a government auction, rather than granted to exporters. The revenues from certificate sales would then be used to finance a reduction in FICA payroll taxes. We report the results of simulations of the alternative plan's effects on macroeconomic balances and GDP growth. Notably, the alternative plan would lessen the severity of the growth recession expected in our base projection.
Keywords: E12; E17; F13; F32; 330; Current Account Deficit; Trade Deficit; Trade Policy; Warren Buffett; Macroeconomic Model